Analysis and implementation of a boost DC–DC converter with high voltage gain and continuous input current. Issue 4 (1st March 2020) - Sedaghati, Farzad; Pourjafar, Saeed
Abstract : In this study, a new high‐voltage gain DC–DC converter based on the coupled inductor and voltage lift circuit technique is proposed. In the suggested converter, a high‐voltage conversion ratio is achieved using a low turn's ratio of the coupled inductor which decreases the volume of core. Also, by selecting the low number of turn's ratio of coupled inductors, the peak voltage through the semiconductors is decreased subsequently. Moreover, the voltage lift circuit is utilised for further increasing the voltage gain and clamping the voltage spike through the main power switch. Zero current switching condition of diodes is another merit of the proposed DC–DC converter, which leads to decrease in the reverse recovery losses generated by diodes. Therefore, the overall efficiency can be enhanced. Technical analysis and comparison surveys with similar topologies are provided to demonstrate the effectiveness of the suggested DC–DC converter. Finally, to validate the performance of the proposed structure, a laboratory prototype with a 200 W power level and 25 kHz operating frequency is implemented.